Stres Berhubungan dengan Kejadian Keputihan pada Mahasiswi Keperawatan Semester 2 - Wilda Atusnah; Yenita agus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between stress and the incidence of vaginal discharge in second-semester nursing students of UIN Syarif Hidayatullah Jakarta. This research method is quantitative research with an analytical design using a cross-sectional approach. The results showed that most of the respondents experienced moderate stress, namely 41 respondents (71.9%) and pathological vaginal discharge as many as 31 respondents (54.4%) with P-value = 0.04 (P <0.05). In conclusion, there is a relationship between stress and the incidence of vaginal discharge in second-semester nursing students. Keywords: Vaginal discharge, Nursing Students, Stress